Global impacts of tropospheric halogens (Cl, Br, I) on oxidants and composition in GEOS-Chem - Sherwen, Tomás; Großmann, Katja (Atmospheric chemistry and physics, 2016)
We present a simulation of the global present-day composition of the troposphere which includes the chemistry of halogens (Cl, Br, I). Building on previous work within the GEOS-Chem model we include emissions of inorganic iodine from the oceans, anthropogenic and biogenic sources of halogenated gases, gas phase chemistry, and a parameterised approach to heterogeneous halogen chemistry. Consistent with Schmidt et al. (2016) we do not include sea-salt debromination. Observations of halogen radicals (BrO, IO) are sparse but the model has some skill in reproducing these. Modelled IO shows both high and low biases when compared to different datasets, but BrO concentrations appear to be modelled low. Comparisons to the very sparse observations dataset of reactive Cl species suggest the model represents a lower limit of the impacts of these species, likely due to underestimates in emissions and therefore burdens. Inclusion of Cl, Br, and I results in a general improvement in simulation of ozone (O3) concentrations, except in polar regions where the model now underestimates O3 concentrations. Halogen chemistry reduces the global tropospheric O3 burden by 18.6 %, with the O3 lifetime reducing from 26 to 22 days. Global mean OH concentrations of 1.28 × 106 molecules cm−3 are 8.2 % lower than in a simulation without halogens, leading to an increase in the CH4 lifetime (10.8 %) due to OH oxidation from 7.47 to 8.28 years. Oxidation of CH4 by Cl is small (∼ 2 %) but Cl oxidation of other VOCs (ethane, acetone, and propane) can be significant (∼ 15-27 %). Oxidation of VOCs by Br is smaller, representing 3.9 % of the loss of acetaldehyde and 0.9 % of the loss of formaldehyde.
Gesehen am 06.05.2020